2021
DOI: 10.3390/met11111813
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Liquid Metal Embrittlement during Resistance Spot Welding of Martensitic Steel with Zn Jet Vapor-Deposited Coating

Abstract: Advanced high-strength steels protected by zinc coatings have contributed to a reduction in CO2 emissions in the automotive industry. However, the liquid metal embrittlement (LME) of the Fe/Zn couple induced by simultaneously acting stresses and high temperatures during resistance spot welding could be the cause of unexpected failure. We investigated the possible risk of LME in spot-welded martensitic steel with Zn jet vapor-deposited coating and its influence on weld strength. The weld nugget cross-sections w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The liquation crack seems to have assisted the crack propagation during the CTT. Other researchers have reported that steels with austenitic microstructures, such as austenitic stainless steel and TWIP steels, have a liquation crack susceptibility [25,29]. Further, adding alloying elements like Mn and C in the AHSS tends to stabilise the austenite phase and widen the partially melted zone (PMZ), promoting the susceptibility of liquation crack formation.…”
Section: Discussionmentioning
confidence: 99%
“…The liquation crack seems to have assisted the crack propagation during the CTT. Other researchers have reported that steels with austenitic microstructures, such as austenitic stainless steel and TWIP steels, have a liquation crack susceptibility [25,29]. Further, adding alloying elements like Mn and C in the AHSS tends to stabilise the austenite phase and widen the partially melted zone (PMZ), promoting the susceptibility of liquation crack formation.…”
Section: Discussionmentioning
confidence: 99%